Short-term outpatient follow-up of vericiguat treatment in patients hospitalized for heart failure - Li, Zihan; Li, Tingting; Liu, Tingxun; Liu, Yuanqiao; Si, Daoyuan; He, Yuquan; Yang, Ping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundVericiguat—a novel oral soluble guanylate cyclase stimulator—was developed for the treatment of chronic heart failure (HF). Although the value of vericiguat therapy in chronic HF has been gradually recognized, its safety and efficacy in the acute phase of HF remain elusive.Methods100 patients with acute HF receiving vericiguat therapy at the China-Japan Union Hospital of Jilin University between September 2022 and June 2023 were retrospectively analyzed. An external control was built from real-world data of acute HF subjects contemporaneously hospitalized in the same hospital using a propensity score matching (PSM) method.ResultsAfter a median follow-up of 68 days, 80 patients completed at least one outpatient follow-up or had an endpoint event and cardiovascular death occurred in 6 patients. We matched 75 external control patients for this purpose. In single-arm study, overall, although systolic blood pressure (SBP) decreased significantly before and after treatment, there was little change in SBP in the SBP low group (baseline SBP less than 120mmHg) (from 109 mmHg to 105 mmHg, p = 0.109). Estimated glomerular filtration rate (eGFR) and serum potassium did not change significantly (p = 0.521 and 0.070, respectively). However, compared with the renal function normal group, eGFR showed a slower downward trend in the renal insufficiency group (p = 0.025). After using the PSM method, significant improvements in left ventricular ejection fraction and N-terminal pro-B-type natriuretic peptide were seen in both groups before and after treatment. There was no significant difference between the two groups. However, the downward trend in eGFR was even less significant in the vericiguat group, with significant differences between the two groups (p = 0.024).ConclusionsVericiguat is feasible in acute HF, even in patients with hypotension and renal dysfunction. At the same time, vericiguat may have a potential renoprotective effect, which warrants further exploration.